Aquaculture and Behavior 2012
DOI: 10.1002/9781444354614.ch9
|View full text |Cite
|
Sign up to set email alerts
|

Fighting and Aggression

Abstract: Aggression (behaviour that actually or potentially causes harm to another animal) is widespread among fishes, often taking the form of territoriality or dominance. The mechanisms that control aggression in fish are described, including the effects of stimuli from opponents, the importance of the context in which an aggressive encounter occurs and the effects of nutritional condition, endocrine status and brain biochemistry. The way aggression changes during development is then considered, evidence given for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 213 publications
(223 reference statements)
1
24
0
Order By: Relevance
“…It has been shown that feeding intervals are strongly correlated with hunger and return of appetite (Riche et al, 2004). Low feeding frequency may lead to increased hunger, intraspecific competition and interindividual FI (Damsgå rd and Huntingford, 2012). When feed availability and accessibility are reduced, the agonistic behaviour tends to increase and feed monopolization tends to be more intense, which may result in disproportional feed acquisition, considerable variation in feed consumption and this ultimately gives rise to differential growth.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that feeding intervals are strongly correlated with hunger and return of appetite (Riche et al, 2004). Low feeding frequency may lead to increased hunger, intraspecific competition and interindividual FI (Damsgå rd and Huntingford, 2012). When feed availability and accessibility are reduced, the agonistic behaviour tends to increase and feed monopolization tends to be more intense, which may result in disproportional feed acquisition, considerable variation in feed consumption and this ultimately gives rise to differential growth.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the number of animals clearly hinders the aggressive behavior quantification for most of those conditions. Furthermore, there are differences in the experimental protocol between those studies that make it difficult to conclude only in terms of high or low density if social hierarchy can be affected by the number of animals in the group, without considering the amount of available food, shelter, and space [5]. Nevertheless, studies combining the effect of stocking density and social aggressive interactions should be conducted in order to allow us a better understanding of its impact on Nile tilapia's welfare.…”
Section: Stocking Densitymentioning
confidence: 99%
“…Social behavior is defined as any kind of interaction between conspecifics, in such a way that it influences their immediate or future behavior [1]. In this conceptual framework, fish social behavior includes reproductive behavior, such as mating and courtship, cooperative interactions [2,3], shoaling [4], and social hierarchy, which is marked by aggressive interactions to reach a certain social rank and to defend territory, as well as environmental resources [5]. Social interaction, however, is not limited to conspecifics, but it can also occur among heterospecifics, such as in client-cleaner coral reef fishes, wherein a species cooperates by cleaning parasites off of another species, thus interacting between them [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, researchers have confirmed that, in certain ontogenetic stages, the environment background color could indirectly influence the increase or decrease of aggression levels in the fish species. Therefore, for rearing in closed systems, changing the color could represent a simple, but an efficient way to ethologically manipulate the fish (Damsgård and Huntingford, 2012).…”
Section: Introductionmentioning
confidence: 99%